ANALISIS PENGARUH TENAGA KERJA, TINGKAT PENDIDIKAN DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI KOTA MAKASSAR TAHUN 2004-2013 - Rusdi, H Muh; Haerati, Haerati (Perpustakaan dan Penerbitan Unismuh Makassar, 2013)
This study aims to determine and analyze how much influence the amount of labor, education and government spending on economic growth in the city of Makassar. The hypothesis is that the amount of labor, education level and government spending have a positive and significant impact on economic growth in Makassar. The type of data used in this study is secondary data. The data is then processed using a computer program that is SPSS 16 with multiple linear regression analysis method. The results showed that the number of labor force, education level and government expenditure had a positive effect on the economic growth in Makassar City, the regression result between dependent variable and independent variable was R-Square = 0,979 and F statistic = 93,880 so that together variable of labor force, and government expenditure has a positive effect on economic growth in Makassar City